Upaya Penguatan Kesadaran Remaja: Sosialisasi Pencegahan Pernikahan Dini di Desa Beji, Andong, Boyolali - Sugiyat, Sugiyat; Azizah, Annafi Nurul; Effendi, Arif; Oktatianti, Tina; Ni’madina, Tien Azhari; Shiddiqi, Muflikhul Awwal Ash (LPMP Imperium, 2025)
This community service activity provides socialization on the prevention of early marriage to teenagers in Dukuh Beji, Beji Village, Andong District, Boyolali Regency, which was held on Saturday, February 1, 2025.The purpose of this activity is to raise teenagers' awareness of the negative impacts of early marriage and the importance of better future planning.The implementation method includes three stages: preparation with coordination with the village government and community leaders, execution with the delivery of material by speakers, interactive discussions, and the screening of educational videos, as well as evaluation.The indicators of success for this activity include active participation of participants in discussions, their understanding of the material measured through Q&A sessions, and enthusiasm in providing feedback.The results of the activity show that participants gained new understanding of the risks of early marriage from health, education, and social aspects.Thus, this activity successfully encouraged teenagers to think more maturely when making decisions related to their future.